Efficacy and Safety of Bevacizumab Plus Erlotinib in Patients with Renal Medullary Carcinoma - Wiele, Andrew J. (Cancers (Basel), 2021)
SIMPLE SUMMARY: Renal medullary carcinoma (RMC) is a rare and highly aggressive renal cell carcinoma, with a median survival of 13 months. Platinum-based chemotherapy is the recommended standard of care for RMC, but no effective salvage regimens have been established to date. Previous comprehensive molecular characterization of RMC tissues revealed a reliance on aerobic glycolysis, suggesting that bevacizumab plus erlotinib may be an effective regimen against RMC. The aim of our retrospective study was to evaluate the efficacy and safety of bevacizumab plus erlotinib in patients with RMC. In ten patients, the combination was safe and effective, establishing bevacizumab plus erlotinib as a new salvage regimen in RMC. ABSTRACT: Purpose: To assess the efficacy and safety of bevacizumab plus erlotinib in patients with RMC. Methods: We retrospectively reviewed the records of patients with RMC treated with bevacizumab plus erlotinib at our institution. Results: Ten patients were included in the study. Two patients achieved a partial response (20%) and seven patients achieved stable disease (70%). Tumor burden was reduced in seven patients (70%) in total, and in three out of five patients (60%) that had received three or more prior therapies. The median progression-free survival (PFS) was 3.5 months (95% CI, 1.8–5.2). The median overall survival (OS) from bevacizumab plus erlotinib initiation was 7.3 months (95% CI, 0.73–13.8) and the median OS from diagnosis was 20.8 months (95% CI, 14.7–26.8). Bevacizumab plus erlotinib was well tolerated with no grade ≥4 adverse events and one grade 3 skin rash. Dose reduction was required in one patient (10%). Conclusions: Bevacizumab plus erlotinib is clinically active and well tolerated in heavily pre-treated patients with RMC and should be considered a viable salvage strategy for this lethal disease.